Applications of Normal S-Iterative Method to a Nonlinear Integral Equation - Gursoy, Faik (HINDAWI LTD, 2014)
It has been shown that a normal S-iterative method converges to the solution of a mixed type Volterra-Fredholm functional nonlinear integral equation. Furthermore, a data dependence result for the solution of this integral equation has been proven.
Keywords: FIXED-POINTS; CONVERGENCE; MAPPINGS; Science & Technology - Other Topics